2014 Annual IEEE India Conference (INDICON) 2014
DOI: 10.1109/indicon.2014.7030430
|View full text |Cite
|
Sign up to set email alerts
|

Statistical approach for distance estimation using Inverse Perspective Mapping on embedded platform

Abstract: The paper presents a real time image processing algorithm for distance estimation on Beagleboard. The system uses a single camera fixed at a stationary position to capture the real time image of target object and determine its distance in contrast to existing and most common vision algorithms of stereo vision.The image captured from a single forward facing camera suffers from high degree of uncertainty in object distance estimation due to the nonlinear relation between object height and its actual distance fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In recent years, research on the methods for estimating the distance of monocular vision vehicles based on geometric models, which are largely divided into the inverse perspective mapping transformation method [3], projection geometric relationship method [5], and fitting modeling method [16], has achieved considerable results. In [4], [17], [18], [20], a distance estimation method based on IPM was proposed. The difference among these studies is the object detection method, such as the road removal algorithm [4], [17], threshold adjustment [18], and hue, saturation, and value (HSV) color mapping [20].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, research on the methods for estimating the distance of monocular vision vehicles based on geometric models, which are largely divided into the inverse perspective mapping transformation method [3], projection geometric relationship method [5], and fitting modeling method [16], has achieved considerable results. In [4], [17], [18], [20], a distance estimation method based on IPM was proposed. The difference among these studies is the object detection method, such as the road removal algorithm [4], [17], threshold adjustment [18], and hue, saturation, and value (HSV) color mapping [20].…”
Section: Related Workmentioning
confidence: 99%
“…In [4], [17], [18], [20], a distance estimation method based on IPM was proposed. The difference among these studies is the object detection method, such as the road removal algorithm [4], [17], threshold adjustment [18], and hue, saturation, and value (HSV) color mapping [20]. The overall idea is to convert the original image into a bird s eye view, which approximates the image obtained from the top-down observation scene.…”
Section: Related Workmentioning
confidence: 99%
“…The system had been tested in various situations and was found to be efficient in distance estimation and object detection. However, it is extremely perceptive to changes in the environmental conditions [6]. It was also found that its tolerance to changes in light intensity can be improved by observing its effect on predicted distance value.…”
mentioning
confidence: 99%
“…Another method evaluated was Inverse Perspective Mapping. This method utilized inverse perspective mapping for distance estimation [5][6]. To predict the distance of the tracked object under various conditions, regression analysis was employed to derive the equation needed [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation